Faculty-Related Challenges in Medical Ethics Education: A Qualitative Study - Morteza Khaghanizade; Hasan Malaki; Mahmood Abbasi; Abbas Abbaspour; Essa Mohamadi (مجله ایرانی آموزش در علوم پزشکی, 2012)
Introduction: Medical ethics education is a key subject in medical occupations, as learning ethics is fundamental for their relationship with patients. Teachers are of the most important elements in medical ethics education, because they are one of the most important factors of forming the morality and the professional character in students. The aim of this study is to explain challenges and problems which threaten the medical ethics education. Methods: Fourteen medical ethics teachers of universities of medical sciences in Tehran took part in this qualitative content analysis study performed in year 2010. Data was collected through semi-structured interviews and analyzed via content analysis approach (Mayring method). Results: The analysis of participants’ interviews led to the extraction of three themes as follows: 1)professional capability of medical ethics teachers 2)medical ethics education using active teaching methods and 3)the gap between teaching in theory and practice. Each of these themes includes several major and minor classifications, each describe a specific aspect of existing challenges in medical ethics teaching related to the teachers. Conclusion: Results indicate that medical educators in general and medical ethics teachers in particular, haven’t been efficient enough in moral development of students. Therefore, short-term professional teaching courses on medical ethics and active teaching methods are suggested to be held for all medical teachers. Besides, all medical teachers are recommended to be obliged to, as behavioral models, facilitate moral and professional development of their students in practice.